2009
DOI: 10.1590/s0102-311x2009000300020
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados a hábitos de saúde bucal e utilização de serviços odontológicos entre adolescentes

Abstract: Estudo transversal com 1.170 adolescentes da sétima série da rede pública municipal de Gravataí, Rio Grande do Sul, Brasil, investigando a associação de fatores sócio-demográficos, psicossociais e relacionados ao estilo de vida com hábitos de saúde bucal e utilização de serviços odontológicos. Os dados foram analisados por regressão de Cox modificada para estudos transversais. As meninas tiveram maior freqüência de escovação dentária assim como aqueles que relataram não se sentirem discriminados ou sozinhos. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
36

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 25 publications
2
24
0
36
Order By: Relevance
“…(one or more days and never) 26 ; • Visits to the dentist: "In the past 12 months, how many times did you go to the dentist?" (once or more and not once) 12 ; • Weekly fruit consumption: "In the past 7 days, on how many days did you eat fresh fruit or fruit salad?" (low consumption: none to four days, and high consumption:…”
Section: Variables Analyzedmentioning
confidence: 99%
See 1 more Smart Citation
“…(one or more days and never) 26 ; • Visits to the dentist: "In the past 12 months, how many times did you go to the dentist?" (once or more and not once) 12 ; • Weekly fruit consumption: "In the past 7 days, on how many days did you eat fresh fruit or fruit salad?" (low consumption: none to four days, and high consumption:…”
Section: Variables Analyzedmentioning
confidence: 99%
“…Health risk behaviors in individuals do not occur in isolation: they tend to add to others 8 . Protection factors for oral health risk behaviors usually correspond to behaviors and patterns related to general health: being a female and having better socioeconomic level, for adults and adolescents [9][10][11][12][13][14] ; parents with higher educational levels, 15 and more family support for adolescents 11,12,16 . RESUMO: Objetivo: Identificar a prevalência da presença simultânea de comportamentos de risco à saúde bucal em adolescentes brasileiros e fatores associados.…”
Section: Introductionmentioning
confidence: 99%
“…A garantia de acesso e a qualificação contínua dos serviços de saúde bucal são imprescindíveis na busca de melhores condições de vida e saúde para nossos jovens 12 .…”
Section: Materials E Métodounclassified
“…The association between sex and oral health was studied by Davoglio et al 28 , who investigated 1,170 students aged between 12 and 18 years old, in the municipal public network of Gravataí, Rio Grande do Sul. The authors observed an association between the frequency of tooth brushing and sex.…”
Section: Indifferentmentioning
confidence: 99%